PERCEPTION AND ATTITUDE TOWARDS ADVERTISING IN ONLINE SOCIAL NETWORKING SITES (SNSS) - ALSoud, Anas Ratib; Johar; MGM; Jaber, Omar Abdel (International Journal of Psychosocial Rehabilitation, 2020)
This work investigate the important factors affecting attitudes towards social networking advertising especially when the social networking users still have negative attitudes towards advertising in social networking sites. The model that was developed proposed that attitudes towards online social networking advertising can be modeled with variables of Credibility, Interactivity, Reference Group, Privacy Concern. The result of this research indicates that the four factors interactivity affect attitudes towards social networking advertising. The other factors such as credibility, reference group, privacy concern do not affect attitudes towards social networking advertising. On the other hand, users have concerns about the credibility of advertising on social networking. This indicates that the low credibility of advertising has not much improved across different media even though it is new. Credibility does not affect attitudes towards social networking advertisings. Results also show that there is no strong correlation between reference groups and attitudes towards online social networking advertising and no strong relationship between privacy concerns and attitudes towards online social networking advertising.